Increasing resident participation in waste management through intrinsic factors cultivation - . Sunarti; J.H. Tjakraatmadja; A. Ghazali; B. Rahardyan (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES:  Resident participation in waste management is essential to overcome waste problems effectively. In many developing countries, the local government has been struggling to encourage resident involvement in the waste management process, but the participation rate is still low. Thus, it requires a system that can encourage residents to participate effectively and sustainably. Therefore, this study aimed to determine what determinant factors, either extrinsic or intrinsic, significantly improve resident participation by changing behaviour toward waste management. METHODS: This study tried to get insights from previous studies about key determinant factors affecting resident behaviour toward waste management to improve participation, significantly using a literature review method. FINDINGS: Educational setting for residents is crucial to improve waste management participation by cultivating key intrinsic factors with support from extrinsic factors that lead to changing behaviour. This study identified eight types of key contents shared in the educational setting to ensure its improvement. Key intrinsic factors should be cultivated, including six kinds of knowledge and five emotional domain factors. The six critical types of knowledge include technical experience, waste management performance knowledge, perception of benefits, environmental awareness, understanding of individual and social responsibility, and understanding the social norms and regulations. The five intrinsic factors in the emotional domain include environmental efficacy, motivation, personal moral norms, PBC, and Attitude toward waste management. All the critical determinant factors, including intrinsic and extrinsic factors, should support each other to improve residents’ behaviour, leading to sustainable participation. CONCLUSION: Relevance of educational content to the residents is crucial to ensure educational intervention effectiveness. With full support from the antecedent factors, waste management behaviour can be nurtured sustainably, significantly increasing the participation rate. Combining extrinsic and intrinsic factors is recommended to ensure the effectiveness of the improvement of resident participation.